Financially-legal description of management methods in the process of work with problem credits in economic activity - Білько, Олександр Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In practice the questions of the legislative adjusting of certain types of collate, realization of politics a bank remain unsolved in relation to the estimation of solvency of borrower, providing of return of the given out credits. Reasons of failure to return of credits can be such as too trustful attitude toward a borrower; off-grade estimation of solvency of borrower; errors are in the estimation of material well-being of loan; an incomplete reflection is in the credit agreement of terms that provide interests of bank, control absence after a borrower in a period the return of credit, uneffective development of credit brief-cases that must be perfected and complement in a period financial crises. Every problem credit has his features, about the origin of difficulties for a borrower identical facts testify: - stopping of contacts with the workers of bank; - presentation of the financial reporting with delays that is not explained; - unfavorable price changes on the action of borrower; - a presence of net losses during one, or a few periods covered; - negative changes of indexes of liquidity, correlation of the personal and attracted funds, business activity; - a rejection of volume of realization of products and money streams from those, that was planned at delivery of credit; - dramatic changes of bits and pieces on the accounts of client, that was not expected and not explained. There are two basic methods of management in the process of work with problem credits: rehabilitation and liquidation. The method of rehabilitation consists in development of general with a borrower plan of measures in relation to the return of credit. The method of liquidation means the return of credit by realization of procedure of bankruptcy and sale of assets of borrower. Liquidation and rehabilitation are expensive enough methods of management problem credits from the point of view of duration of process, financial charges, payment of legal services. Certainly, the best politics from a management losses consists in their avoidance, but, unfortunately, in the real life, attaining it is not succeeded. The existent methods of management problem credits do not diminish them to the volume, there is a requirement in the use of modern instrument of management of banks problem credits. For minimization of volumes of problem credits banks can take advantage of such basic directions of perfection of methods of management a problem debt for to the credits: - creation of separate subdivision from a management problem credits; - automation of organization of process; - the permanent monitoring of information about a client; - timely and adequate reacting on the origin of problem credit, including by his restructuring.